OPTIMALISASI APLIKASI BUSUU DALAM PEMBELAJARAN BAHASA ARAB MANDIRI - Albantani, Azkia Muharom (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2018)
In the age of technological advancement, gadget has an important role in the various activities of a person, no exception in learning. With a variety of applications offered by platform providers, both android and iOS. Now one can learn something independently. Busuu is an application developed to help a person in learning foreign languages independently, such as learning Arabic independently. Learning paths used in this application have been using international standards, ranging from beginner level (A1), basic level (A2), intermediate level (B1), and advanced (B2). This application provides learning materials in the form of audio visual that can improve the four skills of Arabic language. Optimizing the usage of Busuu applications is very likely to prepare someone to be able to communicate in Arabic.